2022
DOI: 10.1016/j.jiac.2022.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Persistent viral shedding of severe acute respiratory syndrome coronavirus 2 after treatment with bendamustine and rituximab: A case report

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA is detectable in nasopharyngeal specimens for up to 12–20 days regardless of the presence of chronic diseases in patients. We report a case of prolonged SARS-CoV-2 infection that lasted for more than eight weeks. The patient had persistent lymphopenia after receiving six cycles of bendamustine and rituximab (BR) therapy for follicular lymphoma; the last chemotherapy session was completed nine months before admission. The first nasopharyngeal spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Since it has been reported that bendamustine reduced CD4-positive T cells, we speculated that bendamustine might impede the serologic response [45]. In fact, there have been several studies on B-NHL patients with COVID-19 severity and mortality who were previously exposed to both anti-CD20 antibody and bendamustine [46][47][48][49][50]. Our results also suggested that these immunocompromised patients have a high risk of COVID-19 infection.…”
Section: Discussionsupporting
confidence: 51%
“…Since it has been reported that bendamustine reduced CD4-positive T cells, we speculated that bendamustine might impede the serologic response [45]. In fact, there have been several studies on B-NHL patients with COVID-19 severity and mortality who were previously exposed to both anti-CD20 antibody and bendamustine [46][47][48][49][50]. Our results also suggested that these immunocompromised patients have a high risk of COVID-19 infection.…”
Section: Discussionsupporting
confidence: 51%
“…Persistent SARS-CoV-2 infection may occur in immunocompromised individuals, and these patients tend to remain infectious for !3 weeks. Table 2 lists reported cases of persistent SARS-CoV-2 infection in patients under anti-CD20 therapy, including this case (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Most case reports are of malignant lymphoma or chronic lymphocytic leukemia, and rarely of other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) pandemic continues to affect the global population. There have been several reports of immunocompromised patients developing persistent and prolonged severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…We then speculated that either the virus in the present case had lost aggressiveness or the acquired anti-SARS-CoV-2 antibodies had restrained proliferation in the respiratory airways. Recently, several cases of COVID-19 after bendamustine and rituximab-treatment have been reported (25)(26)(27)(28). In these reports, even with prolonged viral shedding, the clinical outcomes were not always unfavorable.…”
Section: Discussionmentioning
confidence: 99%